Offering ART refill through community health workers versus clinic-based follow-up after home-based same-day ART initiation in rural Lesotho: The VIBRA cluster-randomized clinical trial. - Alain Amstutz (Public Library of Science (PLoS), 2021)
Background Community-based antiretroviral therapy (ART) dispensing by lay workers is an important differentiated service delivery model in sub-Sahara Africa. However, patients new in care are generally excluded from such models. Home-based same-day ART initiation is becoming widespread practice, but linkage to the clinic is challenging. The pragmatic VIBRA (Village-Based Refill of ART) trial compared ART refill by existing lay village health workers (VHWs) versus clinic-based refill after home-based same-day ART initiation. Methods and findings The VIBRA trial is a cluster-randomized open-label clinical superiority trial conducted in 249 rural villages in the catchment areas of 20 health facilities in 2 districts (Butha-Buthe and Mokhotlong) in Lesotho. In villages (clusters) randomized to the intervention arm, individuals found to be HIV-positive during a door-to-door HIV testing campaign were offered same-day ART initiation with the option of refill by VHWs. The trained VHWs dispensed drugs and scheduled clinic visits for viral load measurement at 6 and 12 months. In villages randomized to the control arm, participants were offered same-day ART initiation with clinic-based ART refill. The primary outcome was 12-month viral suppression. Secondary endpoints included linkage and 12-month engagement in care. Analyses were intention-to-treat. The trial was registered on ClinicalTrials.gov (NCT03630549). From 16 August 2018 until 28 May 2019, 118 individuals from 108 households in 57 clusters in the intervention arm, and 139 individuals from 130 households in 60 clusters in the control arm, were enrolled (150 [58%] female; median age 36 years [interquartile range 30-48]; 200 [78%] newly diagnosed). In the intervention arm, 48/118 (41%) opted for VHW refill. At 12 months, 46/118 (39%) participants in the intervention arm and 64/139 (46%) in the control arm achieved viral suppression (adjusted risk difference -0.07 [95% CI -0.20 to 0.06]; p = 0.256). Arms were similar in linkage (adjusted risk difference 0.03 [-0.10 to 0.16]; p = 0.630), but engagement in care was non-significantly lower in the intervention arm (adjusted risk difference -0.12 [-0.23 to 0.003]; p = 0.058). Seven and 0 deaths occurred in the intervention and control arm, respectively. Of the intervention participants who did not opt for drug refill from the VHW at enrollment, 41/70 (59%) mentioned trust or conflict issues as the primary reason. Study limitations include a rather small sample size, 9% missing viral load measurements in the primary endpoint window, the low uptake of the VHW refill option in the intervention arm, and substantial migration among the study population. Conclusions The offer of village-based ART refill after same-day initiation led to similar outcomes as clinic-based refill. The intervention did not amplify the effect of home-based same-day ART initiation alone. The findings raise concerns about acceptance and safety of ART delivered by lay health workers after initiation in the community. Trial registration Registered with Clinicaltrials.gov (NCT03630549).